Differential efficacy of tyrosine kinase inhibitors according to the types of EGFR mutations and agents in non-small cell lung cancer: a real-world study - Tae-Hwan Kim; Jin-Hyuk Choi; Mi Sun Ahn; Hyun Woo Lee; Seok Yun Kang; Yong Won Choi; Young Wha Koh; Seung-Soo Sheen (BMC Cancer, 2024)
Abstract Background Both first and second-generation EGFR-TKIs are recommended in advanced NSCLC with common EGFR mutations. However, there are few data on the difference in efficacy of EGFR-TKIs based on the type of EGFR mutation and agents. Methods This retrospective real-world study evaluated the outcomes and clinicopathologic characteristics, including the type of EGFR mutations, of 237 advanced NSCLC patients treated with first- or second-generation (afatinib) EGFR-TKIs as first-line therapy. Results The median progression-free survival (PFS) and overall survival (OS) of all patients were 11 months (M) and 25M, respectively. In the univariate analysis, patients with exon 19 deletion (del) (n=130) had significantly longer median OS compared to those with other mutations (L858R: 84, others: 23) (30 vs. 22 M, p=0.047), without a difference in PFS (p=0.138). Patients treated with afatinib (n=60) showed significantly longer median OS compared to those treated with first-generation TKIs (gefitinib: 159, erlotinib: 18) (30 vs. 23 M, p=0.037), without a difference in PFS (p=0.179). In patients with exon 19 del, there was no significant difference in median PFS (p=0.868) or OS (p=0.361) between patients treated with afatinib and those treated with first-generation TKIs, while significantly better PFS (p=0.042) and trend in OS (p=0.069) were observed in patients receiving afatinib in other mutations. Exon 19 del was independently associated with favorable OS (p=0.028), while age >70 years (p=0.017), ECOG performance status ≥2 (p=0.001), primary metastatic disease (p=0.007), and synchronous brain metastasis (p=0.026) were independent prognostic factors of poor OS. Conclusions The EGFR exon 19 del was associated with favorable OS in advanced NSCLC patients receiving first-line EGFR-TKIs. Moreover, in patients with exon 19 del, first-generation TKIs seem to be a reasonable treatment option if osimertinib is unavailable.